Loving justice : legal emotions in William Blackstone's England - Temple, Kathryn, 1955- (New York : New York University Press, 2020)
How do people develop loyalty to the legal system they inhabit? This text focuses on legal emotions in William Blackstone's transformative, bestselling 'Commentaries on the Laws of England' (1765-69), a collection of volumes that deeply impacted English legal culture and became an icon for English common law values across the British Empire.
Previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 11, 2019).
Keywords: Blackstone, William, -- 1723-1780.; Justice in literature; Emotions in literature; Law -- England -- History; Practice of law -- England -- Psychological aspects; Law -- Psychological aspects; Law and aesthetics; Law; Laws of specific jurisdictions & specific areas of law